The Relationship between Plasma Vitamin D Concentration and Blood Pressure in Korean Middle-aged Males: A Cross-sectional Study - Jooyoung KIM; Hyun-Jung PARK; Dong Jun SUNG (Tehran University of Medical Sciences, 2018)
No Abstract####